Agrotech: Penyiraman Tanaman Dan Pemantauan Kadar Air Dalam Tanah Berbasis Internet Of Things - sussi sussi; Sofia; Nurwulan; Dede; Rika; Muhammad; Amri (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Watering is something important in agriculture. In general, watering is done manually where farmers directly water the plants with a hose. The direct watering method takes a long time, farmers have to visit the farm location and cannot be monitored remotely in real-time. The purpose of this research is to make watering plants based on the internet of things (IoT) using NodeMCU ES8266. Soil moisture data is monitored through the Argotech application in real-time. The soil moisture parameter will determine the automatic watering decision which indicates the water pump is in the on or off position. Measurement of quality of service (QoS) carried out in this study is the measurement of throughput and delay. The throughput measurement is carried out to determine the bandwidth used in the Argotech system. Throughput measurements were carried out three times with the results obtained in the morning at 2926.2 bps, in the afternoon at 2926.3 and night at 2943.4 bps. Agrotech's system delay is 483-487 ms. This study concludes that the Argotech system works well, does not require large bandwidth and has a relatively small delay.